Combined effects of cadmium and tetrabromobisphenol a (TBBPA) on development, antioxidant enzymes activity and thyroid hormones in female rats. (1st June 2018) - Yu, Yunjiang; Ma, Ruixue; Yu, Lin; Cai, Ze; Li, Hongyan; Zuo, You; Wang, Zhengdong; Li, Hui
Abstract: Tetrabromobisphenol A (TBBPA) is one of the world's most widely used brominated flame retardants (BFRs) and considered as persistent halogenated contaminant. E-wastes contain a range of toxic chemicals, including BFRs and heavy metals, exerting adverse impacts to human health and environment. Nevertheless, comprehensive evaluation on combined toxicity of these co-existing pollutants is limited. This study conducted a subchronic effects of cadmium and TBBPA on the development and antioxidative defense system as well as thyroid functions in female rats through single and combined exposure at environmentally relevant doses for a 20-day consecutive administration. Body indexes, histopathology, redox status, and thyroid hormones levels were assessed. Slower body weight gains and reduced ovary weight (20.8% and 32.4% for combined and single-Cd exposures, respectively) were observed with significant variation from controls in high dose treatments. Co-exposure resulted in a slight enhancement in TSH levels compared to control (by 7.6% for high dose) without significance. TBBPA-Cd interactions are involved in the changes of kidney weight as well as the induction of SOD activities and MDA levels. The disturbances in the redox status may be a result of an independent effect of Cd and/or TBBPA and also of their interaction. The results implied under these treatment, kidney was more sensitive with significant increased organ coefficient and alteration for antioxidative indices (increasing by 46% for SOD activity). This study represents the toxic effects of Cd and TBBPA co-exposure through oral administration in pubertal rats, which may provide useful information for health risk assessment for young exposed individuals. Highlights: A subchronic exposure of TBBPA and Cd was conducted in pubertal SD female mice. Body index, redox status and thyroid functions were evaluated. Both single and joint exposures could increase oxidative stress. The effects of co-exposure on liver were more significant than those on kidney. The changes for body index were mainly influenced by CdCl2 .